Halal, PIRT & business finance training for Gambir Anom’s MSME Group, Sidoarjo - Nur Ravita Hanun; Rima Azara; Indah Apriliana Sari W. (Community Empowerment, 2022)
The community of Keboan Anom Village, Gedangan District, Sidoarjo Regency, engages in a constructive activity that was started by the Gambir Anom UMKM group. These initiatives include the formation of a food and beverage company run by Gambir Anom residents. Unfortunately, they have a number of issues, such as the absence of a PIRT, a lack of halal certification, and inadequate business financial management. The implementation of this activity is done through assistancing and training. Through this assistance, the Gambir Anom MSME Group already has a business license and a product license, so that their products are ready to compete in the modern market. Additionally, training with SME accounting software can help business actors understand how to manage their finances.